Field effectiveness of microbial larvicides on mosquito larvae in malaria areas of Botswana and Zimbabwe. (December 2016) - Mpofu, Mulamuli; Becker, Piet; Mudambo, Kaka; Jager, Christiaan
Abstract Background The successful control of malaria vectors requires the control of both the larval and adult stages. The adult control methods through indoor residual spraying (IRS) and use of long-lasting insecticidal nets (LLINs) continue to be widely used with some high measure of success. Larval control methods are also being used by a number of National Malaria Control Programmes (NMCPs) with limited understanding of its contribution. Larval control might be needed in some areas to move from malaria control to elimination. This experimental study was conducted to assess the field effectiveness of winter larviciding on the larval stages of the mosquito in Botswana and Zimbabwe. Methods Two villages were selected in each of the two countries, one as an intervention and the other as the control. Water bodies in the intervention villages were treated using the commercial product VectoBac® WG (Valent BioSciences Corporation, IL, USA) containing the active ingredientBacillus thuringiensis var.israelensis (Bti ), a WHO recommended bio-larvicide, applied at a rate of 300 g per hectare. Random-effects Poisson regression was employed during data analysis to compare intervention with control sites with respect to larval counts. Results The average marginal effect of larviciding on the mosquito larvae taking interaction with time (period) into account, was −1.94 (95% CI −2.42 to −1.46) with incidence rate ratio of 0.14, thus an 86% larval reduction attributable to the intervention for both countries combined. There was a 92% and 65% effect for Botswana and Zimbabwe respectively. The effect on the early larval and late stages was 77% (P < 0.001) and 91% (P < 0.001), respectively. Overall, intervention larval sampling points had five more larvae than the control at baseline and 26 less after 16 weeks. The effect on the different species also showed similar trends. Discussion/conclusion Larval control usingBti showed a high effect on the population of the mosquito larvae. The reduction of the early and late larval stages can lead to reduced adult mosquito emergence and low adult mosquito densities. Larviciding can be used to control mosquito vector population by suppressing the larval stages thereby reducing adult emergence and malaria risk.